Implementation of Standards of Good Pharmacy Practice in the World: A Review - Unhurian, Liana (Asian Journal of Pharmaceutics (AJP), 2018)
The aim of the study is to review the historical stages of development of the requirements of good pharmaceutical practice (GPP), generalization of the normative documents recommended by the International pharmaceutical company (MFP) for use in the world of pharmaceutical practice. Methods of generalization of the information material and system analysis were used in the study. Historical stages of the development of the concept of the GPP in the world and the role of the World Health Organization and the FIP in the process were analyzed. Researches of professional standards of pharmacy practice in developed countries reveal different approaches to the regulation of such activities, however, despite the applicable model standards are developed by the pharmaceutical associations and are used by regulatory bodies, business owners, and professionals to control the quality of pharmacy services that are provided to the population. The study indicates that the development of the GPP standards should be resolved at the level of public professional organizations as the national regulation of pharmacy practice in different countries varies significantly. Prospects of further scientific researches are aimed on using the results of the study while developing and implementing national standards of the GPP in the world.